The Effect of Birthing Ball on the Pain Scale of First Stage of Labor in the Active Phase in the Bukit Sari Health Center Work Area - Nyimas Siti Nurlaila, Linda; Hanifah, Fatya Nurul; Fadhilah, Siti (Universitas Prima Indonesia, 2025)
Labor pain is a feeling and emotional reaction that begins with regular contractions, helping to open the birth canal. It can lead to higher blood pressure, heart rate, and breathing rate. Unmanaged pain can increase worry and anxiety. This research sought to evaluate how a birthing ball influences labor discomfort during the initial active stage. The research design is a pre-experimental one-group pretest-posttest. The study population includes 45 active phase I maternity mothers. Accidental sampling is used, with a sample size of 28 people. Univariate analysis uses a frequency distribution table, and bivariate analysis uses the Wilcoxon test. Based on the results of the study obtained an average of labor pain in mothers before the intervention, as many as 26 people (92.9%) respondents were in severe pain. After the intervention, the average labor pain of 21 people (75%) of respondents decreased to moderate pain. Based on the test mc near test between pretest and posttest values ​​obtained a p-value of 0.000 (p<0.05) so that it can be concluded that there is an influence of birth ball in reducing the pain scale of maternity mothers during the first active phase. The birth ball reduces the pain scale of maternity mothers in the first active phase.